Prevention and control of COVID-19 infection at the community health center during the new normal era - Daktari, Gilang Ferara; Hidayat, Wahyu; Suryanti, Netty (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Due to the coronavirus disease (COVID-19) pandemic, community health center services were limited. It was critical to have health protocols as a reference for the prevention and control of COVID-19 infection during adaptation in the new normal in Bandung City. The purpose of this research was to determine the prevention and control of COVID-19 infection at community health center in the new normal. Methods: A cross-sectional study was conducted utilizing observation through questionnaire with chosen yes (if appropriate) or no (if not appropriate) based questions in checklist form. Inclusion criteria was active dentist in community health center and exclusion criteria dentist was not completely answer question in checklist form. Purposive sampling was used to choose 30 dentists for the research sample. Data analysis uses frequency distribution and is divided into four stages, which are: preparatory, pre-visit, visiting, post-visiting stage. Data analysis uses frequency distribution. Results: At the preparatory stage were appropriate: Air flow setting on average 50%; clean water management 100%; room arrangement and management 50%. At the pre-visit stage were appropriate: Management of tele-dentistry detection and screening average 67%; patient treatment scheduling management 100%. The visiting patient stages were appropriate: detection and screening during patient visit only measurement of patients body temperature 100%; The concept of four handed dentistry 43.3%; implementation of isolation precaution in dentist personal protective equipment average 92.2% and in transmission precaution average 85%. At the post visit patient stages were appropriate: cleaning the workplace average 85%; Medical equipment management 100%; Medical waste treatment average 87.7%. Conclusion: During adaptation of the new normal, the implementation of prevention and control of COVID-19 infection in dental and oral health services community health center is not in accordance with the protocol. Improvements are still needed on several stages.Keywords: Dentist, community health center, prevention and control of COVID-19 infection, new normal.